Thomas Glassford. (1st August 2013) - Colpitt, Frances
Thomas Glassford's "Pteridomania" provoked a knot of contradictions, simultaneously attracting and repel- ling the viewer with its gaudy beauty. Born in Laredo, Texas but now resident in Mexico City, the artist often employs Mexican craftsmen for their facility with a variety of domestic materials. His characteristic choices have included vinyl upholstery, patent leather, chrome hardware, anodized aluminum, fluorescent lights, and melamine dishware (in contrast to the natural materials of dried gourds, tanned leather, and porcelain that he used in the early 1990s), which are distinguished as much by seductive tactility, brilliant color, and reflective surfaces as by distasteful cheapness and artificiality.